2013
DOI: 10.1177/1062860613476733
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the Physician Quality Reporting System in an Academic Multispecialty Group Practice

Abstract: The Centers for Medicare and Medicaid Services (CMS) introduced the Physician Quality Reporting System (PQRS) in 2007. PQRS was developed as a value-based, pay-for-reporting initiative intended to increase quality and decrease costs. Jefferson University Physicians (JUP) was an early participant in this voluntary program. In this article, the policy context for CMS's launch of PQRS and JUP's implementation strategy, lessons learned, and an account of benefits and barriers to participation are reviewed. In 2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…With the implementation of MIPS and a purported shift of practice of medicine from individual authority to societal accountability, the quality of medical practices continue to be under increasing and continuous scrutiny, not only by policy makers, but peers, payers, and patients (9,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). The strategy developed by IOM in the early years to improve quality of care known as pay for performance or financial incentives to transform behaviors to achieve greater value substantially changed to PQRS and now quality measures as a component of MIPS (18,(33)(34)(35)(36). MIPS substantially altered PQRS measures with the ability to provide non-PQRS or non-MIPS measures to provide meaningful quality measurements.…”
Section: Quality Performance Measuresmentioning
confidence: 99%
“…With the implementation of MIPS and a purported shift of practice of medicine from individual authority to societal accountability, the quality of medical practices continue to be under increasing and continuous scrutiny, not only by policy makers, but peers, payers, and patients (9,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). The strategy developed by IOM in the early years to improve quality of care known as pay for performance or financial incentives to transform behaviors to achieve greater value substantially changed to PQRS and now quality measures as a component of MIPS (18,(33)(34)(35)(36). MIPS substantially altered PQRS measures with the ability to provide non-PQRS or non-MIPS measures to provide meaningful quality measurements.…”
Section: Quality Performance Measuresmentioning
confidence: 99%
“…17 Preliminary results from the application of PQRS to individual physicians have demonstrated that the modest incentives (which were initially part of this program, but ended after 2014) are significantly offset by the implementation and maintenance costs of the program. 8 CMS recently reported that 76.9% of the 2889 neurosurgeons who participated in PQRS in 2013 were eligible for incentive payments, which averaged only $731. 11 Unfortunately, the majority of measures that are included in the traditional CMS-approved PQRS measure set are generic and process oriented, and concerns have been raised about their relevance to true clinical quality.…”
Section: Physician Quality Reporting System: Requirements For Satisfamentioning
confidence: 99%
“…They believe that they create additional administrative costs and are thus expensive to participate in. [2][3][4][5][6][7] They believe that they do not lead to quality improvement. 4,8,9 Nearly 84 % of physicians do not believe that Medicare quality reporting programs enhance their ability to provide patients with high quality care.…”
Section: Introductionmentioning
confidence: 99%